2000
DOI: 10.1246/cl.2000.294
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the NO/C3H8/O2 Reaction by Using H2 over Ag/Al2O3 Catalysts under Lean-Exhaust Conditions

Abstract: We examine the effect of H2 on the selective reduction of NO by C3H8 over Ag/Al2O3 catalysts under lean-exhaust conditions. The NO reduction activity caused by C3H8 at low temperature (590-760 K) is greatly increased by adding H2 in the presence of excess oxygen and water vapor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
82
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(90 citation statements)
references
References 11 publications
8
82
0
Order By: Relevance
“…13,159,160 In the presence SO 2 , the deteriorated Recently, it was found that the presence of H 2 significantly enhanced the low temperature activity of Ag-based catalysts for NO x reduction by hydrocarbons. 17,40,[209][210][211] Up to now, however, the interpretation of the H 2 promotional effect on HC-SCR has been under debate. To increase the rate of NO x conversion, basically, the hydrogen must accelerate the rate(s) of the slow step(s) in the reaction of HC-SCR, while the slow step(s) are likely to vary depending on the reaction temperature and feed conditions.…”
Section: Reactivity Of Intermediates Originating From Partial Oxidatimentioning
confidence: 99%
“…13,159,160 In the presence SO 2 , the deteriorated Recently, it was found that the presence of H 2 significantly enhanced the low temperature activity of Ag-based catalysts for NO x reduction by hydrocarbons. 17,40,[209][210][211] Up to now, however, the interpretation of the H 2 promotional effect on HC-SCR has been under debate. To increase the rate of NO x conversion, basically, the hydrogen must accelerate the rate(s) of the slow step(s) in the reaction of HC-SCR, while the slow step(s) are likely to vary depending on the reaction temperature and feed conditions.…”
Section: Reactivity Of Intermediates Originating From Partial Oxidatimentioning
confidence: 99%
“…To achieve the practical use, a SCR catalyst should also have a high level of activity for NO x reduction at lower temperature, considering the typical temperatures of diesel exhausts and cold-start driving cycle. Modification of the reaction atmosphere by adding H 2 to an HC-SCR system could be useful because of the surprising promotional effect on the SCR of NO x over Ag/Al 2 O 3 catalyst [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the activity of Ag/Al 2 O 3 for the SCR of NO x by C 2 H 5 OH in the low temperature range is still insufficient to be considered as a potential method for NO x abatement from exhaust gases of diesel engines. Nevertheless, a recent report [7] indicated that the addition of hydrogen to the feed gas resulted in a remarkable improvement of the NO x reduction at temperatures below ca. 623 K using a series of lower alkanes (alkenes) as reductants.…”
Section: Introductionmentioning
confidence: 99%